False positive result of human chorionic gonadotropin caused by human anti-mouse antibodies - Racek, Jaroslav; Potočová, Ivana; Rajdl, Daniel; Trefil, Ladislav; Šolcová, Marie (Biochemia medica, 2023)
Immunochemical reactions are fast, can be automated, and generally do not require pretreatment of biological material. Based on these advantages, they are widely used. On the other hand, they are susceptible to analytical interference that can lead to inaccurate results. These factors include the presence of anti-mouse antibodies, causing false positive (or sometimes false negative) results. Although the anti-mouse antibodies over many decades have been repeatedly identified to be the causative source but due to the rarity of such encounters they remain insufficiently considered. Here we show a case, a 45 year-old female who was mis-diagnosed with pregnancy due to falsely elevated human chorionic gonadotropin (hCG) due to anti-mouse antibodies. This led to the patient undergoing two ultrasound examinations and laparoscopy before the hCG was repeated on alternative assays which showed negative results, preventing the patient from methotrexate treatment. Here we describe the details of the case, outline the assay principal, supporting the finding from literature and outlining a process on how to identify such interferences in timely manner.
Keywords: lidé středního věku; lidé; Female; falešně pozitivní reakce; Pregnancy; False Positive Reactions; těhotenství; Antibodies; Middle Aged; choriogonadotropin; protilátky; Chorionic Gonadotropin; ženské pohlaví; Humans